Pengembangan Bahan Ajar Teks Debat Berbasis Sosial Politik Siswa Kelas X SMA - Syauqi, Muhammad Abrar; Ali, Ali; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop a socio-political-based debate text learning module for class X SMA. Following the 3D model (Define, Design, and Development) proposed by Thiagarajan, the module underwent validation by four experts, including two material experts and two design experts. Utilizing a Likert scale questionnaire, the validation sheet assessed material and design aspects. The material's quality received an average score of 3.60 from the first material expert, deemed "valid and good," and 3.55 from the second material expert, also "valid and good." Design assessment yielded an average of 4.44 from the first expert and 4.25 from the second expert, both indicating "valid and very good." Based on these evaluations, the socio-political debate text learning module is deemed feasible for use, meeting the criteria of validity and quality in both material and design aspects.